Enteral Nutrition Management in the Critical Care Patient: Intensive Care Nurses’ Practices of Tube Feeding - Seferoğlu, Nuri; Özyürek, Pakize; Gürlek Kisacik , Öznur (Progress in Nutrition, 2021)
Study Objectives: Maximizing the benefits of enteral nutrition (EN) and minimizing adverse events requires adequate training of the multidisciplinary team, especially nurses, and systematic practice of care practice. This study was aimed at determining the EN practices of intensive care unit (ICU) nurses in Turkey and the factors affecting these practices. Methods: “Nurse Information Form" and the "Enteral Nutrition Practice Form" were distributed to 196 intensive care unit nurses to investigate the EN. Results: The total score of the nurses on EN practice was 126.82 ± 16.18 (range, 35-175). Only 34.6% (n = 68) of the participants were found to have an acceptable score of sufficiency for positive EN practices. The highest practice score ICU nurses obtained subsections was the “Preventing Complications Related to EN” (4.19 ± 0.50) subsection, the lowest score was also "Gastro-Intestinal System (GIS) Tolerance Evaluation" (2.72 ± 0.68) subsection. While 50.5% of the nurses never paid attention to the amount of product that should be given to the patient at a meal, 23.0% of them never paid attention to the fact that medication that should not be crushed was not given through the feeding tube. Conclusion: It was concluded that ICU nurses do not follow the current guidelines on EN practice and have not received adequate training in EN. With a well-designed in-service training program and standard protocols, adherence to evidence-based guidelines can be increased; inconsistencies and errors in the EN practices can be reduced.